(untitled) (KULT_online, 2016)
In Alexander Friedrich’s monograph “Metaphorologie der Vernetzung,” on the terminological and metaphorical uses of network concepts ranging from antiquity through to network society, these are discussed and clarified within their historical and logical relationships. The genesis of the meaning of modern networks is traced by using a new metaphorological method, namely the “stratigraphy” of cultural lead-metaphors. The model shows how lifeworld phenomena have been depicted with net-metaphors in various historical contexts and how these became layers of within modern application, first as an epistemic and then as cultural lead-metaphor.